Driveability Simulation of Vehicle with Variant Tire Properties - Lukac, Michal; Brumercik, Frantisek; Krzywonos, Leszek (Communications - Scientific Letters of the University of Zilina, 2016)
The aim of the presented article is to show the possibilities of vehicle tire mathematical model creation and present simulations of a typical driving manoeuvre of a vehicle model equipped with variant tire models.
Keywords: tire; vehicle; simulation